Water resources specifications in national and district level hydro economic models of Pakistan: A presentation for Pakistan Water Week - Davies, Stephen; Akram, Iqra; Ali, Muhammad Tahir (International Food Policy Research Institute, 2024)
A Keynote presentation for the Session on “Hydro-economic Modeling for Effective Climate Smart Water Management.” Pakistan Water Week Conference November 4-8, 2024.